Effect of Extraction and Preservation Methods on the Microbiological and Physicochemical Quality of Pentadesma butyracea Butter Produced in a Traditional Area in Benin - Marius Eric Badoussi; Yann E. Madode; Célestin K. C. Tchekessi; Laurenda Honfozo; Ifagbémi Bienvenue Chabi; Kamirou Chabi Sika; Arlette Adjatin; Joseph D. Hounhouigan; Paulin Azokpota (Journal of Food Quality)
P.butyracea butter, produced by different traditional methods, is often stored for further use in different types of packaging which may affect its quality. The present work aims to evaluate the effect of the production method and the type of packaging used on the physicochemical and microbiological quality of butter during storage. The extraction of Pentadesma butter was first carried out through production monitoring in three repetitions by three different butter producers according to the two most used traditional production methods. Then, butter from production was stored for three months in four types of packaging (aluminium bowls, calabashes, baskets, and black polyethylene bags) in the production environment. The microbiological and physicochemical quality of the stored butter was assessed at 0, 30, 60, and 90 days using normative reference methods. The production method and the type of packaging used had a significant effect on the variation of free fatty acid content (1.54 ± 0.07%–2.6 ± 0.2%), peroxide value (0.96 ± 0.09°meq·O2/Kg–3.9 ± 0.7°meq·O2/Kg), and colour of the butter during storage. In contrast, only the type of packaging material influenced the microbiological characteristics of the butter during storage. After three months of storage, the yeast and mould load was out of the standard range in all packages, i.e., 2.53 ± 0.4 log°CFU/g, 2.9 ± 0.2 log°CFU/g, 4.67 ± 0.2 log°CFU/g, and 1.4 ± 0.2 log°CFU/g for aluminium bowls, calabashes, baskets, and black polyethylene bags, respectively. The aerobic mesophilic germ load was within the standard in black polyethylene bags (3.22 ± 0.08 log°CFU/g), in contrast to the other packages (4.23 ± 0.08 log°CFU/g–6.45 ± 0.13 log°CFU/g). This shows that black polyethylene bags are the best packaging to guarantee the quality of butter. It is important to continue this investigation by storing butter for a longer period of time with more appropriate packaging.